The effect of aerobic exercise on metabolic and inflammatory markers in breast cancer survivors-a pilot study. - KENNEDY, MICHAEL; CONNOLLY, ELIZABETH; WALSH, JULIE; GUINAN, EMER (My University, 2013)
Physical activity is associated with a reduced risk of breast cancer development and recurrence. There are several hypothesised mechanisms for this including positive effects on metabolic and inflammatory biomarkers and favourable changes in anthropometric variables. This pilot study examined the effect of an 8-week aerobic exercise intervention on several of these outcomes, including body composition, the metabolic syndrome, C-reactive protein (CRP) and physical activity, in breast cancer survivors 2–6 months post-chemotherapy. Methods Assessments were completed at baseline, at 8-weeks and 3-months post-intervention. Measures taken following a 12-h fast included body composition (bioimpedance analysis), metabolic syndrome (waist circumference, blood pressure, high-density lipoprotein cholesterol, triglycerides and fasting glucose), insulin resistance (homeostatic model assessment), CRP and physical activity (accelerometry and questionnaire). Participants were randomized to either an 8-week moderate-intensity aerobic exercise group or a usual-care control group. Analysis was completed using repeated-measures analysis of variance (ANOVA) (p = 0.05). Results Twenty-six breast cancer survivors participated (mean (standard deviation) age 48.1 (8.8) years, exercise group; n = 16, control group; n = 10). At baseline, 13 participants were overweight, 6 were obese and 19 centrally obese. Intention-to-treat analysis revealed no significant differences between the exercise and control groups in any of the outcomes measures; however, analysis of those who adhered to >90 % of the supervised exercise class showed a significant decrease in waist circumference (p = 0.05) and a significant increase in subjectively reported “total weekly” (p = 0.005) activity. Conclusion While this 8-week aerobic exercise pilot intervention did not elicit significant improvements in biomarkers of breast cancer risk, there was some suggestion of improvements in waist circumference and subjectively measured physical activity in participants with >90 % adherence to the programme. A trial of longer duration and greater subject numbers is warranted.
PUBLISHED
Keywords: Cancer survivors; Cancer